Coordination analysis of cross-flow heat exchanger under high variations in thermodynamic properties. (October 2017) - Guo, Jiangfeng; Huai, Xiulan
Highlights: Matrix analysis is employed to analyze performance of cross-flow heat exchanger. Heat exchanger performance also depends on the coordination between parameters. The better coordination between parameters means the more heat load. Coordination angle represents the coordination degree in heat exchanger matrix. Abstract: Supercritical pressure CO2 was employed to investigate the improvement of a cross-flow heat exchanger with variable properties in the present work. The whole heat exchanger was uniformly divided into M × N heat exchange units, and the matrix analysis indicated that the total heat load of the heat exchange matrix depends not only on the vector norms of local heat transfer coefficient and local temperature difference, but also on their distributed coordination. A numerical example confirmed that the total heat load increased as the coordinative degree between the two vectors of local heat transfer coefficient and local temperature difference improved when the other conditions remained unchanged. The further analysis indicated that the coordination improvement between the two vectors of local heat flux density and local heat transfer area also increased the total heat load. A coordination angle was proposed to measure the coordination degree between the distributions of different parameters in heat exchange matrix; the smaller coordination angle means the better distributed coordination when the other conditions remain the same. The present work might provide a new approach to the improvement of heat exchange matrix for the fluids with drastic changes of properties.